2017
DOI: 10.1016/j.antiviral.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

The cholesterol transport inhibitor U18666A inhibits type I feline coronavirus infection

Abstract: Feline infectious peritonitis (FIP) is a feline coronavirus (FCoV)-induced fatal disease in wild and domestic cats. FCoV exists in two serotypes. Type I FCoV is the dominant serotype worldwide. Therefore, it is necessary to develop antiviral drugs against type I FCoV infection. We previously reported that type I FCoV is closely associated with cholesterol throughout the viral life cycle. In this study, we investigated whether U18666A, the cholesterol synthesis and transport inhibitor, shows antiviral effects a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 39 publications
4
60
0
1
Order By: Relevance
“…Our previous study demonstrated that the triazole antifungal agent itraconazole blocks the intracellular trafficking of cholesterol and inhibits type I FCoV infection in a feline cell line (felis catus whole fetus-4 cells: fcwf-4 cells) [12]. Similar results were observed with U18666A, the widely studied cholesterol transport inhibitor [11]. Other researchers reported that itraconazole and U18666A blocked cholesterol egress from late endosomes [13][14][15].…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…Our previous study demonstrated that the triazole antifungal agent itraconazole blocks the intracellular trafficking of cholesterol and inhibits type I FCoV infection in a feline cell line (felis catus whole fetus-4 cells: fcwf-4 cells) [12]. Similar results were observed with U18666A, the widely studied cholesterol transport inhibitor [11]. Other researchers reported that itraconazole and U18666A blocked cholesterol egress from late endosomes [13][14][15].…”
Section: Introductionsupporting
confidence: 67%
“…Based on the above results and our previous study [11,12], different FCoV serotypes may enter feline cells through different endocytic routes: FCoV-I KU2 is released from late endosomes into the cytosol, whereas FCoV-II 79-1146 is released from early endosomes into the cytosol. Cholesterol accumulation was previously reported to disrupt late endosome function [16,17].…”
Section: The Effects Of Late Endosomal Function On Fcov In Fcwf-4 Cellssupporting
confidence: 61%
See 2 more Smart Citations
“…We suggest that our understanding of FIP should consider the presence of these two distinct viruses, in order to determine whether or not it has implications in clinical settings. Such distinctions are suggested based on documented differences seen in cell culture between type I and type II viruses, for example with regard to interferon responses and the activity of antiviral drugs [30,31].…”
Section: Introductionmentioning
confidence: 99%